2014
DOI: 10.1016/j.carbon.2013.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Single wall carbon nanotubes loaded with Pd and NiPd nanoparticles for H2 sensing at room temperature

Abstract: Pd and bimetallic Ni 50 Pd 50 nanoparticles protected by polyvinylpyrrolidone (PVP) have been synthesized by the reduction-by-solvent method and deposited on single wall carbon nanotubes (SWCNTs) to be tested as H 2 sensors. The SWCNTs were deposited by drop casting from different suspensions. The Pd nanoparticles-based sensors show a very reproducible performance with good sensitivity and very low response times (few seconds) for different H 2 concentrations, ranging from 0.2 to 5 % vol. H 2 in air at atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 43 publications
5
30
1
Order By: Relevance
“…15,24 After their purification, the NPs were loaded on SiO 2 and Ti-SiO 2 (UV-Vis inactive and active supports, respectively) to study their catalytic activity in AB…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation
“…15,24 After their purification, the NPs were loaded on SiO 2 and Ti-SiO 2 (UV-Vis inactive and active supports, respectively) to study their catalytic activity in AB…”
Section: 23mentioning
confidence: 99%
“…22,23 In the present work, Pd and Co x Pd 1-x NPs were prepared by the well-established procedure of the reduction by solvent method using PVP as capping agent and following an already reported procedure. 15,24 After their purification, the NPs were loaded on SiO 2 and Ti-SiO 2 (UV-Vis inactive and active supports, respectively) to study their catalytic activity in AB Fig. 1).…”
mentioning
confidence: 99%
“…It should be noted, however, that the procedure described in this manuscript does not require a lengthy or aggressive treatment for the carbon nanostructures. In addition, the amount of surfactant used is almost two orders of magnitude lower than other reports in which CNT suspensions were obtained by the use of surfactants (Bravo-Sanchez et al, 2010;García-Aguilar et al, 2014). Considering that the concentration of the resulting suspensions is comparable to those reported in the literature, our approach to employ a pH-switchable surfactant opens up new possibilities in the field on CNT inks and thin films preparation.…”
Section: Discussionmentioning
confidence: 79%
“…Given their chemical nature, carbon-based nanomaterials show very poor dispersability in water. To overcome this problem, two main strategies have been reported in the literature: some authors have observed that the use of polymers, which combine a polar end (which may interact with water) with a non-polar end (which may interact with the carbon surface) in combination with a water-soluble polymer gives rise to stable suspensions of CNTs (or "inks," as the authors point out) (Bravo-Sanchez et al, 2010;García-Aguilar et al, 2014). On the other hand, and so as not to introduce a large amount of surfactant species in the suspensions, other authors have made use of the surface chemistry of carbon nanomaterials, modifying their functional groups with a strong acid such as HNO 3 or HNO 3 /H 2 SO 4 mixtures, which in turn led to the preparation of stable suspensions, which are pH sensitive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation